Progression in teaching beginning swimming: Rank order by degree of difficulty - Junge, M.; Blixt, T.; Stallman, R. K. (Biomechanics and Medicine in Swimming XI, 2010)
"Teach first things first"! But what comes first? Where do we start? Also, children are different and no progression will suit all. However, it should be possible to a) agree on content and b) find a progression that suits a majority. Children 5-6 yrs of age (N=146) received 18 hrs of instruction, in small groups. A theoretical progression of 19 skills was created from the international literature, examining course content of leading educational organizations. A single head instructor coordinated all teaching. Evaluation of progress and recording of criterion success on the 19 skills was overseen by the same head instructor. The number of children succeeding on each skill was deemed a reflection of the degree of difficulty. The actual rank order of skills derived from these learners was correlated to the theoretical rank order using Spearman`s rank order correlation. Rho proved to be 0.97. Among other results, all (paired) skills on the front proved easier than the corresponding skill on the back. Arguements are presented to defend retaining the theoretical rank order as well as arguements for adjusting the rank order. However, when individualising teaching, there seems to be an optimal progression for each child, albeit slightly different from one child to another. It was surmised that degree of difficulty may not be the only criterion to be used when creating a progression.